2000
DOI: 10.1159/000008238
|View full text |Cite
|
Sign up to set email alerts
|

Eye Deviation in Patients with One-and-a-Half Syndrome

Abstract: To understand malalignments of the visual axes in one-and-a-half syndrome, we measured eye positions in 4 patients with this syndrome under two conditions: with Frenzel goggles to prevent eye fixation and without Frenzel goggles. When fixation was prevented with the Frenzel goggles, all patients showed mild outward deviation in both eyes. Removal of the Frenzel goggles elicited adduction of the eye ipsilateral to the side of the lesion for fixation, with greater outward deviation of the contralateral eye (acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
3
0
2
Order By: Relevance
“…Central facial paralysis (75%), hemiparesis or hemiplegia (30%), hemihypoesthesia (30%) are the most common accompanying findings (3,4). Peripheral facial paralysis is another clinical finding that accompanies one-anda-half syndrome due to the anatomic structure of the nerve, as seen in our case.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Central facial paralysis (75%), hemiparesis or hemiplegia (30%), hemihypoesthesia (30%) are the most common accompanying findings (3,4). Peripheral facial paralysis is another clinical finding that accompanies one-anda-half syndrome due to the anatomic structure of the nerve, as seen in our case.…”
Section: Discussionsupporting
confidence: 59%
“…Lesions in this area that involve the ipsilateral 6 th cranial nerve, PPRF, and MLF together cause one-and-a-half syndrome. PPRF and MLF lesions may cause this syndrome without involvement of this nerve nucleus because the 6 th cranial nerve and PPRF fibers converge (3,4). In one-and-ahalf syndrome, horizontal eye movements are lost at the side of the lesion; when looking to the contralateral side, only the contralateral eye can abduct and nystagmus is seen in that eye.…”
Section: Discussionmentioning
confidence: 99%
“…Bir buçuk sendromu nadiren izole bir bulgudur. Olgularda santral fasiyal paralizi (%75), hemiparezi veya hemipleji (%30), hemihipoestezi (%30) en sık görülen diğer nörolojik bulgulardır (5)(6)(7).…”
Section: Discussionunclassified
“…[1415] Similarly, an outward deviation in the contralesional eye can result from an imbalance of PPRF signals. [16] Another contradiction to the concept of medial rectus subnucleus involvement in WEBINO has come from the observations that exotropia also occurs ipsilaterally in unilateral INO, that is, in the WEMINO syndrome. Among four patients with WEMINO described by Johnston and Sharpe, pathologic analyses obtained for one patient showed that the lesion was confined to the pontine tegmentum.…”
Section: Discussionmentioning
confidence: 99%